Signifikansi Deklarasi Kuasa Sebelum Peristiwa Terangkatnya Yesus Ke Surga - Serepina Yoshika Hasibuan (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
The basic question in this research is how to understand the significance of the declaration of power in the events leading up to Jesus' ascension to Heaven? Does this declaration of power only have significance for the mission movement or does it actually involve something broader? The purpose of this study is to examine more deeply the significance of the declaration of power just before the event of the Lord Jesus' ascension to Heaven. Common interpretations often link the importance of this declaration of power in the realm of carrying out the mission of the Great Commission. The author through this article wants to explore the deeper meaning of the declaration of power in the Lord Jesus, Father and in the giving of power to Jesus' disciples through narrative analysis. The research in this article was conducted using a qualitative method by conducting a narrative analysis on the text of Mat. 28:16-20 and Acts. 1:6-11. Based on the study conducted, the results found that the significance of the declaration of power is not only as an impetus for preaching the Gospel but also in reversing the paradigm of the kingship of Jesus, fellowship between believers, victory over satanic power, and the basis for miracles.